Tinjauan Vibrio Vulnificus sebagai Ancaman Emerging Foodborne Disease pada Makanan Laut Segar - Sanam, Maxs U. E.; Gelolodo, Maria Aega; Tangkonda, Elisabet; Loe, Fhady R. (JURNAL KAJIAN VETERINER, 2023)
Vibrio vulnificus is a crucial foodborne opportunistic pathogen that can cause wound infections, septicemia, and gastroenteritis with a 50% fatality rate. This bacteria occurs in estuaries and coastal waters and is found in large quantities in oysters and other mollusc shells. The increasing number of foodborne diseases worldwide is suspected to have occurred due to the expansion of the international food trade. Consumption of raw seafood, especially oysters containing Vibrio vulnificus bacteria, can result in acute, severe systemic infections and is responsible for 95% of deaths from seafood consumption in the United States. The diagnosis of Vibrio vulnificus infection is confirmed by the growth of the bacteria in culture media from wounds, feces or blood. This article discusses the characteristics of the bacteria, host, environment, transmission, pathogenesis, clinical symptoms, diagnostic techniques and geographical distribution of V. vulnificus.